2012
DOI: 10.4236/ojpm.2012.23044
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of youth risk behaviors with norm-consciousness and resilience among Japanese high school students

Abstract: The purpose of this study was to examine the influences of norm-consciousness and resilience on the prevention of youth risk behaviors among Japanese high school students. Data of a national survey, Japan Youth Risk Behavior Survey 2011, was used for this analysis. The subjects were 9778 students (5027 males, 4751 females) in grades 10 -12 in 102 schools randomly selected from among high schools throughout Japan. When multiple regression analysis was carried out using four subdomains of norm-consciousness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…In agreement with the present results, Lang et al was reported higher PA adolescents had likely better sleep (41). A signi cant association was shown between normal sleepers with good food habits (regular breakfast frequency, no snacking, no sweetened beverage consumption) in French primary school children (12) and low prevalence of risk behaviors (lack of vigorous PA, skipping breakfast) in high school students (42). Also, in other studies, a signi cant positive association was illustrated between normal sleepers with fat mass%, waist circumference, and normal weight (8, 12).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the present results, Lang et al was reported higher PA adolescents had likely better sleep (41). A signi cant association was shown between normal sleepers with good food habits (regular breakfast frequency, no snacking, no sweetened beverage consumption) in French primary school children (12) and low prevalence of risk behaviors (lack of vigorous PA, skipping breakfast) in high school students (42). Also, in other studies, a signi cant positive association was illustrated between normal sleepers with fat mass%, waist circumference, and normal weight (8, 12).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the present results, Lang et al was reported higher PA adolescents had likely better sleep (41). A significant association was shown between normal sleepers with good food habits (regular breakfast frequency, no snacking, no sweetened beverage consumption) in French primary school children (12) and low prevalence of risk behaviors (lack of vigorous PA, skipping breakfast) in high school students (42). Also, in other studies, a significant positive association was illustrated between normal sleepers with fat mass%, waist circumference, and normal weight (8,12).…”
Section: Chen Et Al Was Reported a Significant Relationship Between supporting
confidence: 92%
“…Even the effect of the habit of eating breakfast with suicidal attempts has not been well reported, its association on mental health is documented. Among those, one study conducted with American Indian/Alaska Native (AI/AN) and non-AI/AN youth, demonstrating eating breakfast every day has a protective effect on suicide attempts; [15] other studies in Japan demonstrated the skipping of breakfast is associated with shorter sleeping time [16] and in South Korea, it is associated with suicidal attempts among adolescents [17]. At present, no study shows a dose effect, frequency of eating breakfast per week on suicidal attempts and the relative effect on boys and/or girls.…”
Section: Introductionmentioning
confidence: 99%